Screening of oleaginous yeasts for lipid production using volatile fatty acids as substrate. (July 2020) - Llamas, Mercedes; Dourou, Marianna; González-Fernández, Cristina; Aggelis, George; Tomás-Pejó, Elia
Abstract: Using residual material instead of sugars as substrate for oleaginous microorganisms is a promising approach that may reduce the production costs of microbial lipid. In this study, five oleaginous yeasts were screened for their ability to grow and produce lipid utilizing volatile fatty acids (VFAs), generated from anaerobic fermentation of microalgal biomass, as the only carbon and energy source. Yeasts growth and lipid accumulation capacity at three VFAs concentrations (i.e. 5, 10 and 15 g L −1 ) were evaluated. Regardless of VFAs concentration four of the five strains were able to grow in digestates reaching biomass yields from VFAs between 0.22 and 0.37 g g −1 . The highest lipid content in dry biomass was observed in Cutaneotrichosporon curvatum and Cyberlindnera saturnus (36.9 and 33.9% on dry biomass, respectively) corresponding to lipid yields from VFAs of 0.11 and 0.13 g g −1, respectively. Oleic, palmitic and linoleic acids were the major fatty acids, accounting for more than 70% of the fatty acids contained in total yeast lipids, profile similar to that of common vegetable oils. The above findings suggest that microalgal biomass derived VFAs could be converted into yeast lipid suitable as feedstock in the chemical (including biofuel) industry. Highlights: Yeasts use volatile fatty acids from anaerobic fermentation as carbon source. Five oleaginous yeasts showed differences in growth and lipid accumulation. The highest lipid content was provided by C. curvatu s and W. saturnus. Obtained lipid yields were comparable to the achieved with sugar-based substrates. Organic wastes bioconversion to microbial oils is a feasible technology.